1985
DOI: 10.1302/0301-620x.67b3.3997956
|View full text |Cite
|
Sign up to set email alerts
|

The myth of muscle balance. A study of relative strengths and excursions of normal muscles about the foot and ankle

Abstract: The lower limbs of five cadavers were dissected and the lengths of the muscle fibres and the weights of all the muscles below the knee were measured. From this information the relative strength and excursion of each muscle was determined. We found that the plantarflexors of the ankle were six times as strong as the dorsiflexors. We have therefore discarded the concept of "muscle balance" in tendon transfer surgery and propose that task appropriateness should be the guide. The constant relationship between musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
7

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(125 citation statements)
references
References 1 publication
0
118
0
7
Order By: Relevance
“…The FDL tendon was considered to be suitable since the excursion and work percentage of peroneus brevis and FDL are similar. 25 The symptoms resolved in these two patients and both were free from pain except for some mild lateral ache in one after extensive walking, probably due to calcaneocuboid degeneration which had been noted on preoperative radiographs. Both patients had no instability of the hindfoot and were able to return to their previous level of activity, including golf.…”
Section: Discussionmentioning
confidence: 65%
“…The FDL tendon was considered to be suitable since the excursion and work percentage of peroneus brevis and FDL are similar. 25 The symptoms resolved in these two patients and both were free from pain except for some mild lateral ache in one after extensive walking, probably due to calcaneocuboid degeneration which had been noted on preoperative radiographs. Both patients had no instability of the hindfoot and were able to return to their previous level of activity, including golf.…”
Section: Discussionmentioning
confidence: 65%
“…FDLT transfer is thus considered less likely to result in additional disability. FDLT is accessible as it is close anatomically to the tibialis posterior tendon but has the disadvantage that FDL has only half the strength of FHL and a quarter of the strength of tibialis posterior (Silver et al, 1985). Some authors have used FHL successfully with no reported weakness of push-off (Goldner, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] If the first metatarsal was still plantar flexed following these two procedures, a peroneus longus to peroneus brevis tendon transfer was performed to reduce plantar flexion of the first ray. 29,30 Through a 5 cm incision proximal to the tip of the lateral malleolus (Fig. 3b), the peroneus longus tendon was divided and sutured to the peroneus brevis tendon 31 with no.…”
Section: Methodsmentioning
confidence: 99%